Evaluation of Hydrological Drought Characteristics for Bearma Basin in Bundelkhand Region of Central India. (2016) - Swetalina, N.; Thomas, T.
Abstract: Drought is a natural hazard that can have severe impacts on a variety of sectors and at a variety of scales. The Bundelkhand region in Central India has been under the grip of continuous and recurrent drought in the recent years. This has caused large scale economic losses and severe hardships for the local population leading to large scale out-migration and massive poverty in the entire region. Even though the drought starts with the deficit in rainfall, but it ultimately translates into hydrological drought which indicates the reduced water availability in the rivers and groundwater aquifers. The scientific analysis of the hydrological drought is one of the many primary necessity for the development of an effective drought management plan for a region. The hydrological drought characteristics have been evaluated for Bearma basin located in the Bundelkhand region using the variable threshold level approach. The dependable flow in the river at 75% dependability (Q75) for each month has been computed to arrive at the variable threshold level. It has been observed that hydrological droughts of varying severities occurred during 27 years out of the total period of analysis spanning 35 years from 1974-75 to 2008-09. The most severe hydrological droughts were observed during 1978-79 and 2002-03 with a combined severity of -238.26 MCM and -210.39 MCM respectively.